Can we assess muscle balance? - Tillberg, N. (1997)
In this paper, I am going to firstly define different terminologies regarding muscle performance, which are commonly seen in the literature and are important to understand when talking about assessing muscular performance. Secondly, the different methods of assessing muscle, advantages and disadvantages, when to use them and the validity and reliability will be defined and discussed. Finally, a review of test results from assessing muscular performance, definition of normal-abnormal results and clinical implications will be discussed.